The Canonical Form in Murky Waters: Idiom Variation and the Croatian National Corpus - Parizoska, Jelena (Array, 2010)
Stability of form has been established in phraseology as one of the salient characteristics of idioms. Corpus-based studies have relativized this notion, showing that a number of idioms are in fact variable in form and may possess several institutionalized variations. A case in point is the Croatian idiom loviti u mutnom (lit. to hunt in the murk-LOC ; ‘ to obtain something dishonestly’ ), which appears as lov/loviti/lovac u mutnom. The aim of this paper is to show that a combination of factors – corpus evidence, grammatical construction and motivation – are crucial in determining the canonical form and variations. More specifically, on the basis of the data from the Croatian National Corpus, we will prove that loviti u mutnom is a schematic idiom whose variations systematically reflect the underlying ICM MUTNA VODA (‘ murky water’ ), which constitutes its conceptual core. The results show that various lexical and syntactic realizations of the idiom are constrained by the extensions and elaborations of the model motivating it and/or combinations with other models. The variability of the idiom in question raises the issue of the criteria used in establishing the canonical form and the dictionary citation-form in terms of frequency and prototypicality.